Induction and synchronization of estrus in Jersey cows treated with PGF2alpha by two different routes - DUGWEKAR, Y G; PATEL, D M; SARVAIYA, N P; PATEL, A V (The Indian Journal of Animal Reproduction, 2023)
The results of present study suggested the superiority of i.m. treatment of PG as compared to ivsm treatment forinduction of luteolysis in cows.
Keywords: Synchronization of estrus; PGF2alpha; ivsm route; progesterone